A Hole-Tolerant Redundancy Scheme for Wireless Sensor Networks - Juhua Pu; Yu Gu; Yi Zhang; Jia Chen; Zhang Xiong (International Journal of Distributed Sensor Networks)
Maximizing network lifetime while not sacrificing coverage and connectivity in wireless sensor networks (WSNs) has attracted many researches during the past few years. One common approach is node scheduling which dynamically schedules some redundant nodes to shut down and keeps alive some necessary nodes to preserve network performance. Previous researches focus either on guaranteeing coverage and connectivity or sacrificing coverage and connectivity to conserve energy. In this paper, we introduce a new hole-tolerant redundancy scheme (HRS) which can prolong network lifetime while maintaining coverage and connectivity performance. This HRS scheme can tolerate some coverage holes when determining redundancy eligibility, so it shuts down more nodes when hole tolerance is higher. Our work takes into account both homoradius WSNs and heteroradius WSNs. The simulation results show that (1) the average coverage percentage varies mildly but network lifetime is prolonged as hole tolerance increases; (2) HRS outperforms several existing lifetime maximization schemes.